EP117/#763 Application of shallow whole genome sequencing to identify therapeutic opportunities in p53abn endometrial cancers. (4th December 2022) - Jamieson, Amy; Barros, Juliana Sobral De; Cochrane, Dawn; Douglas, Maxwell; Leung, Samuel; Thompson, Emily; Senz, Janine; Lum, Amy; Kobel, Martin; Gilks, Blake; Huntsman, David; Mcalpine, Jessica
Abstract : Objectives: Shallow whole genome sequencing (sWGS) has been successfully used to derive copy number (CN) signatures in high grade serous ovarian cancer (HGSOC), recognizing two signatures associated with homologous recombination deficiencies (HRD). p53abn ECs share genomic features with HGSOC, supporting application of this platform to stratify this aggressive EC molecular subtype. Methods: DNA was extracted from formalin fixed paraffin embedded (FFPE) tumor cores of 203 p53abn ECs and sWGS performed. CN signatures were derived from absolute copy numbers using Rascal (relative to absolute copy number scaling tool). CN amplification of CCNE1 and ERBB2 was called based on CN alterations ≥5, and comparisons were made to CCNE1 and HER2 immunohistochemistry (IHC). Results: HRD-related signatures 3 and 7 were found in 42 p53abn ECs (30 and 12 respectively) encompassing 26% of the 161 cases where CN signatures could be assigned. CN amplification in CCNE1 was identified in 26/203 (13%) with CCNE1 IHC overexpression (2/3+) found in 64% of cases. ERBB2 amplification was observed in 22/203 (11%) with HER2 IHC overexpression (2/3+ on whole stained sections) in 21% and significant intratumor heterogeneity was noted. Conclusions sWGS is a relatively inexpensive tool that can be performed on FFPE, and may be used to identify opportunities for PARPi therapy, with 26% of p53abn EC identified as having HRD signatures. Opportunities for anti-HER2 therapy and targeting CCNE1 (Wee1i) were also identified, although IHC detected a significantly greater proportion of p53abn ECs overexpressing HER2 and CCNE1 compared to CN amplification calls on sWGS. This may, in part, be explained by intratumor heterogeneity.